The reproductive biology of swordfish ( Xiphias gladius) in the Strait of Gibraltar - Abid, Noureddine; Laglaoui, Amin; Arakrak, Abdelhay; Bakkali, Mohammed (Journal of the Marine Biological Association of the United Kingdom, 2018)
During the period from April to September for the years 2014–2016, 998 swordfishes caught by the Moroccan artisanal longline fishery in the Strait of Gibraltar were sampled to study the reproduction of this species in this mixing area between the Mediterranean Sea and the North Atlantic. The results showed that the sex ratio is slightly in favour of males for sizes smaller than 130 cm LJFL (Lower jaw-fork length), whereas females are more numerous in sizes larger than 140 cm LJFL. Fifty per cent of females were estimated to be mature at 170 cm LJFL, while for males, the size at first maturity was estimated to be 95 cm LJFL. The swordfish spawn from June to September, probably in the Mediterranean Sea. The findings of this study suggest that the reproductive characteristics of swordfish caught in the Strait of Gibraltar are similar to those of the Mediterranean swordfish, and a high mixing rate between the Mediterranean and the North Atlantic stocks occurs in the study area.